Gender Leadership in Accelerating Stunting Reduction: Women’s Participatory Governance in Serang Regency, Banten Province - Ida Rosida; Mansyur Achmad; Megandaru W. Kawuryan; Andi Masrich (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Stunting remains a critical public health challenge in Indonesia, particularly in regions with pronounced gender inequalities in household decision-making. Serang Regency recorded one of the highest stunting prevalence rates nationally, at 39.43% in 2019, making it a priority area for accelerated intervention. Objective: This study examines gender leadership in handling stunting in Serang Regency, Banten Province, and constructs an evidence-based model for gender-responsive stunting management. Methods: A qualitative descriptive design was employed. Data were collected through in-depth interviews with 15 key informants selected via purposive sampling, six months of field observations, and document analysis of regulatory instruments, including Regent Regulation No. 40/2021 and nutrition monitoring data from SSGI and e-PPGBM. Data validity was ensured through source triangulation, method triangulation, and member checking. Results: The findings indicate that gender leadership is a determining factor in stunting prevention. Female leadership strengthens multi-stakeholder coordination through participatory and empathetic approaches, improves family health literacy, and addresses structural gender blindness in policymaking. Barriers include limited women’s representation in decision-making, gender-biased household norms, and constrained frontline resources. Conclusion: The gender leadership model rests on four pillars: women’s strategic leadership, community-based women’s leadership, gender-responsive policies, and community education for shared family roles—each reinforced by psychological dimensions. These findings provide practical guidance for local governments in designing sustainable stunting reduction strategies.